2016
DOI: 10.2196/publichealth.6517
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of Unrecognized Atrial Fibrillation in Rural India: An Innovative Community-Based Cross-Sectional Screening Program

Abstract: BackgroundAtrial fibrillation, the world’s most common arrhythmia, is a leading risk factor for stroke, a disease striking nearly 1.6 million Indians annually. Early detection and management of atrial fibrillation is a promising opportunity to prevent stroke but widespread screening programs in limited resource settings using conventional methods is difficult and costly.ObjectiveThe objective of this study is to screen people for atrial fibrillation in rural western India using a US Food and Drug Administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
0
19
1
Order By: Relevance
“…By contrast, in a previous pilot study, we screened 353 Indian adults aged 50 years or older at their homes for five consecutive days. [21] We found a markedly higher prevalence of AF (5.1%) among screened individuals but our limited sample size did not meet the inclusion criteria for the systematic review of sample size of ≥ 750. [16] The present study used a technology-assisted, community-based AF screening strategy to determine the prevalence of AF among adults over the age of 45 years, with a further breakdown according to predefined age-and sex-strata.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…By contrast, in a previous pilot study, we screened 353 Indian adults aged 50 years or older at their homes for five consecutive days. [21] We found a markedly higher prevalence of AF (5.1%) among screened individuals but our limited sample size did not meet the inclusion criteria for the systematic review of sample size of ≥ 750. [16] The present study used a technology-assisted, community-based AF screening strategy to determine the prevalence of AF among adults over the age of 45 years, with a further breakdown according to predefined age-and sex-strata.…”
Section: Introductionmentioning
confidence: 69%
“…Detailed sample size calculations for this study are described elsewhere but a sample size of 1823 was necessary to estimate overall AF prevalence with 1% error assuming the a pirori prevalence of AF to be 5% based on the pilot study; similarly, a minimum of 300 participants in each stratum was needed to estimate the prevalence with 2% error. [21,22] Therefore, residents of villages were approached for participation in the study until seven participants in each stratum from each village were enrolled, totaling 2100 participants from 50 villages. Only four participants with a previous diagnosis of AF were identified by this strategy, and all four refused to participate in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In another large study by Pak‐Hei Chan where the prevalence of atrial fibrillation was low (2.7%), the sensitivity of the device was only 71.4%. The utility of the device was demonstrated in a community‐based setting for detection of atrial fibrillation and for detection of QT interval. …”
Section: Resultsmentioning
confidence: 99%
“…Early findings revealed a prevalence of atrial fibrillation substantially greater than previously reported in India and comparable with that found in the United States and other high-income countries. Although large-scale and more representative screening efforts are currently underway, noteworthy findings from the feasibility study were presented by a trainee-leader [A.S.] at the National Institutes of Health Special Topics Conference on Healthcare Innovations and Point-of-Care Technologies and were published in a leading mobile health journal 31 . A grant proposal, coauthored by the trainee-leaders, to leverage public health infrastructure to establish a systematic screening program for atrial fibrillation was selected among the finalists for joint consideration by the National Institutes of Health and Indian Department of Biotechnology, but ultimately was not funded.…”
Section: Trainee-led Twinning Model For Global Healthmentioning
confidence: 99%